2010
DOI: 10.1002/hed.21349
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of “clear versus revised margins” in oral and pharyngeal cancer

Abstract: Patients receiving repeated resection had the same survival rate as patients who had the tumor resected immediately with negative margins. The use of frozen sections yields a benefit for 15.6% of the operated patients and increases the overall 5-year survival rate by 2% to 3%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 17 publications
1
25
2
3
Order By: Relevance
“…In an historical study by Byers et al, no significant difference in local control was observed between patients with negative frozen section margins and those intraoperatively re‐resected . Similarly, a study by Kwok et al found that tumors for which R0 status had been achieved upon intraoperative completion had a similar outcome to those with primarily R0 margins . In our study, however, positive intraoperative margins were significantly associated with local recurrence, regardless of completeness of re‐excision.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In an historical study by Byers et al, no significant difference in local control was observed between patients with negative frozen section margins and those intraoperatively re‐resected . Similarly, a study by Kwok et al found that tumors for which R0 status had been achieved upon intraoperative completion had a similar outcome to those with primarily R0 margins . In our study, however, positive intraoperative margins were significantly associated with local recurrence, regardless of completeness of re‐excision.…”
Section: Discussioncontrasting
confidence: 56%
“…To provide an R0 resection in oral cancer, fresh frozen section examination has been implemented, and when performed by experienced pathologists has an accuracy in excess of 90% . However, there are conflicting data regarding the role of frozen section margin analysis in oral oncology . As a result, no consensus has been reached on how patients with initially involved fresh frozen margins with cleared margins achieved upon completion of resection should be considered by the MDT in terms of further treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, appropriate margins are difficult to achieve, most notably due to the inability to visualize individual cancer cells during surgery and the heterogeneity in the biologic behavior of the malignant cells . What is widely accepted is that malignant disease left behind after oncologic surgery leads to recurrent disease and poor outcomes . Several investigations examining the impact of surgical margins have demonstrated poor oncologic outcomes associated with positive margins .…”
Section: Introductionmentioning
confidence: 99%
“…malignant disease left behind after ablative oncologic surgery leads to recurrent disease and adversely affects outcomes [8,9] . The literature is clear that in order to maximize survival, reduce recurrence, and improve quality of life for patients undergoing oncologic head and neck surgery, negative margins are paramount [10][11][12][13][14] .…”
Section: Reviewmentioning
confidence: 99%